Interruption of regular dental visits during the COVID‐19 pandemic due to concerns regarding dental visits was associated with periodontitis in Japanese office workers. (25th August 2021) - Iwasaki, Masanori; Usui, Michihiko; Ariyoshi, Wataru; Nakashima, Keisuke; Nagai‐Yoshioka, Yoshie; Inoue, Maki; Kobayashi, Kaoru; Nishihara, Tatsuji
Abstract: Objective: To investigate the interrelationships among concerns regarding dental visits, the status of regular dental visits, and periodontal health during the coronavirus disease 2019 (COVID‐19) pandemic. Background: Continuous oral health care and regular dental visits are important for maintaining periodontal health. Due to the possibility of contracting COVID‐19, individuals have been reluctant to visit medical institutions. It is unclear how the periodontal health of the Japanese population has been affected by the interruption of regular dental visits during the COVID‐19 pandemic and how concerns regarding dental visits have affected attendance at regular dental visits. Methods: This study included 199 Japanese office workers in one municipal office at Fukuoka Prefecture, Japan (average age = 42.6 years; age range = 19–77 years; 123 men and 76 women). Periodontitis was defined based on a full‐mouth periodontal examination. The status of regular dental visits during the COVID‐19 pandemic and concerns regarding dental visits were obtained via questionnaire. We tested the hypothesis that concerns regarding dental visits would indirectly affect periodontal health through the interruption of regular dental visits during the COVID‐19 pandemic. We used mediation analysis, in which concerns regarding dental visits (present or absent) were set as the exposure, periodontitis (present or absent) was set as the outcome, and the status of regular dental visits (continued during the COVID‐19 pandemic or not) was set as the mediator. Results: Of the 199 study participants, 108 had a habit of attending regular dental visits. Of these, 31 (28.7%) discontinued regular dental visits during the COVID‐19 pandemic. Compared to the individuals who continued regular dental visits, those who discontinued regular dental visits had a higher prevalence of periodontitis (49.4% vs 77.4%, p  < 0.05) and concerns regarding dental visits (22.1% vs 64.5%, p  < 0.05). Discontinuing regular dental visits significantly mediated the association between concerns regarding dental visits and periodontitis (natural indirect effect: odds ratio = 1.68, 95% confidence interval = 1.02–2.79, proportion mediated = 64.3%). Conclusion: The study results showed that individuals who discontinued regular dental visits during the COVID‐19 pandemic due to concerns regarding dental visits had relatively poor periodontal health.